2009
DOI: 10.1161/strokeaha.108.532556
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Monocyte Chemoattractant Protein-1 Deficiency on Cerebral Aneurysm Formation

Abstract: Background and Purpose-Recent studies have suggested that chronic inflammation actively participates in cerebral aneurysm (CA) formation. Macrophages accumulate in CA walls and express proinflammatory genes promoting CA progression, but the molecular mechanisms of monocyte/macrophage recruitment into CA walls remain to be elucidated. Methods-Monocyte chemoattractant protein-1 (MCP-1) expression in experimentally induced CAs was assessed by immunohistochemistry and Western blotting. The role of MCP-1 in CA form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
238
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(261 citation statements)
references
References 44 publications
(41 reference statements)
20
238
1
2
Order By: Relevance
“…In addition, the study found increased plasma concentrations of MCP-1 in unruptured aneurysms. [23] This reaffirms the work of Aoki et al [24] who observed increased MCP-1 expression in rat arterial walls. These data indicate that inflammatory cells are being actively recruited to the aneurysm wall as a result of high chemokine levels, further contributing to IA formation and eventual rupture.…”
Section: Mediators Of Inflammationsupporting
confidence: 83%
“…In addition, the study found increased plasma concentrations of MCP-1 in unruptured aneurysms. [23] This reaffirms the work of Aoki et al [24] who observed increased MCP-1 expression in rat arterial walls. These data indicate that inflammatory cells are being actively recruited to the aneurysm wall as a result of high chemokine levels, further contributing to IA formation and eventual rupture.…”
Section: Mediators Of Inflammationsupporting
confidence: 83%
“…22 To examine the chronic inflammation in CA walls, we assessed the macrophage infiltration and responsible molecules, VCAM-1 and MCP-1. VCAM-1 was the adhesion molecule responsible for transendothelial migration of macrophages and MCP-1 was a major chemoattractant for macrophages.…”
Section: Mcp-1 and Vcam-1 Expression And Subsequentmentioning
confidence: 99%
“…Especially, in a series of studies, the crucial contribution of a long-lasting 'chronic' inflammation to the pathogenesis of IAs has been demonstrated and thus nowadays IA is considered as a chronic inflammatory disease affecting intracranial arteries. Notably, we and others have revealed involvement of macrophages, which are the most abundant inflammatory cells detected in IA lesions of both human and animal models [1,2], to progression of IAs through regulating inflammatory responses in situ [3,4]. For example, the pharmacological depletion of macrophages [3] and genetic deletion of a chemoattractant for macrophages [3,4], MCP-1, both significantly suppress inflammatory responses in lesions and IA.…”
Section: Targeting Macrophages To Treat Intracranial Aneurysm Tomohirmentioning
confidence: 86%
“…Notably, we and others have revealed involvement of macrophages, which are the most abundant inflammatory cells detected in IA lesions of both human and animal models [1,2], to progression of IAs through regulating inflammatory responses in situ [3,4]. For example, the pharmacological depletion of macrophages [3] and genetic deletion of a chemoattractant for macrophages [3,4], MCP-1, both significantly suppress inflammatory responses in lesions and IA. Thus, a macrophage itself, factors mediating macrophage infiltration or ones functioning in macrophage to evoke inflammation can become a therapeutic target for IAs.…”
Section: Targeting Macrophages To Treat Intracranial Aneurysm Tomohirmentioning
confidence: 86%